2006
DOI: 10.1111/j.1467-789x.2006.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated body mass index and mortality risk in the elderly

Abstract: The purpose of this report was to perform a systematic review and meta-analysis of the studies examining the impact of an elevated body mass index (BMI) on mortality risk in elderly (> or =65 years) men and women. A variance-based method of meta-analysis was used to summarize the relationships from available studies. The summary relative risk of all-cause mortality from the 26 analyses that included a risk estimate for a BMI within the overweight range was 1.00 (95% confidence intervals, 0.97-1.03). The summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
224
1
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(257 citation statements)
references
References 74 publications
(64 reference statements)
25
224
1
6
Order By: Relevance
“…For overweight, 75% of HRs with measured weight and height and 67% of HRs with self-reported weight and height were below 1. These results are broadly consistent with 2 previous meta-analyses 114,115 that used standard categories. In a pooled analysis of 26 observational studies, McGee et al 114 112 and 26% in England.…”
Section: Commentsupporting
confidence: 82%
“…For overweight, 75% of HRs with measured weight and height and 67% of HRs with self-reported weight and height were below 1. These results are broadly consistent with 2 previous meta-analyses 114,115 that used standard categories. In a pooled analysis of 26 observational studies, McGee et al 114 112 and 26% in England.…”
Section: Commentsupporting
confidence: 82%
“…This is consistent with other studies that have shown that older adults at normal or below normal BMIs have lower survival than those who are overweight or even obese. 21 We considered 12 measures of function: dependency in at least one activity of daily living (ADL: bathing, dressing, eating, getting in or out of bed or chairs, and using the toilet); dependency in at least one instrumental activity of daily living (IADL: handling household chores, doing necessary business, shopping or getting around for other purposes); any reported difficulty with (1) walking 1/4 mile, (2) walking up ten steps, (3) standing or (4) sitting for 2 h, (5) stooping, (6) reaching above the head, (7) grasping small objects, (8) lifting/carrying 10 pounds, (9) pushing/pulling large objects, or (10) going out to do things like shopping.…”
Section: Factors Of Interestmentioning
confidence: 99%
“…Obesity prevalence in middle-aged and older adults continues to increase worldwide and has doubled since 1980 (1,2) . However, there is controversy surrounding the effects of overweight and obesity in older people, with many studies showing that being overweight, as defined by BMI of 25-29 kg/m 2 , does not appear to be as harmful in the elderly as in middle-aged populations and may even be associated with lower, rather than higher, mortality (3)(4)(5) . In addition, a large body of evidence indicates that overweight and obesity (BMI ⩾ 25 kg/m 2 ) are associated with increased survival in patients with CVD and in particular those with heart failure, an unexpected finding termed the obesity paradox (6)(7)(8)(9)(10) .…”
mentioning
confidence: 99%